Effect of Grade Retention in First Grade on Psychosocial Outcomes - Wu, Wei (2010)
In a 4-year longitudinal study, the authors investigated effects of retention in first grade on children’s externalizing and internalizing behaviors; social acceptance; and behavioral, cognitive, and affective engagement. From a large multiethnic sample (n = 784) of children below the median on literacy at school entrance, 124 retained children were matched with 251 promoted children on the basis of propensity scores (probability of being retained in first grade estimated from 72 baseline variables). Relative to promoted children, retained children were found to benefit from retention in both the short and longer terms with respect to decreased teacher-rated hyperactivity, decreased peer-rated sadness and withdrawal, and increased teacher-rated behavioral engagement. Retained children had a short-term increase in mean peer-rated liking and school belongingness relative to promoted children, but this advantage showed a substantial decrease in the longer term. Retention had a positive short-term effect on children’s perceived school belonging and a positive longer term effect on perceived academic self-efficacy. Retention may bestow advantages in the short-term, but longer term detrimental effects on social acceptance may lead to the documented longer term negative effects of retention.